Impact of Polyherbal Extract (HAMACK) On Anti-Oxidative Markers in Benign Prostatic Hyperplasia Induced Rats - Chidimma Lilian Asadu; Robert Ikechukwu Uroko; Stanley Mary Ubenyi (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
The effects of a polyherbal extract, HAMACK, on antioxidant defences were assessed in with male albino rats with testosterone propionate-induced BPH. Thirty rats (148–156g) were acclimatized and grouped into 6. Group one served as the normal control (2 ml/kg distilled water), while BPH was induced in Group two. Group three received finasteride (5 mg/kg), Groups 4 and 5 were administered with 350 and 700 mg/kg HAMACK respectively, while Group 6 was administered 700 mg/kg alone. Antioxidant status was assessed by measuring reduced glutathione (GSH), glutathione peroxidise, superoxide dismutase, catalase, and glutathione S-transferase (GST). In addition, malondialdehyde (MDA) was determined as a marker of lipid peroxidation. BPH induction significantly (P< 0.0001) reduced antioxidative markers, with a concurrent increase in MDA, confirming oxidative stress. Treatment with finasteride and polyherbal extract significantly (P< 0.0001) restored antioxidant parameters and reduced MDA levels dose-dependently. Additionally, group administered with 700 mg/kg HAMACK alone exhibited the highest antioxidant activity, characterized by elevated antioxidant enzymes alongside reduced MDA. In summary, the polyherbal extract effectively ameliorates oxidative stress associated with BPH by enhancing enzymatic and non-enzymatic antioxidant defences and reducing lipid peroxidation. Its efficacy suggests strong potential therapy for oxidative stress-mediated prostate conditions.